Vidaus prekybos tinklo raida lietuviškose gubernijose 1861-1914 metais: išvežiojamoji ir išnešiojamoji prekyba - Ambrulevičiūtė, Aelita (Lietuvos istorijos studijos, 2009)
Till the 1861 years reforms town’s and township’s dwellers bought goods usually at dolly-shops, shops, markets, and marts. Village dwellers bought items from itemsman’s or in the alehouse. Merchants, townspeople, tradesmen used to sell self-made production from workshops or in the markets and marts. Noblemans organized trade at the alehouse. Peasants handled rarely. Only the most sophisticated and minded peasants were engaged in commercial activity. Under the serfdom conditions, mighty merchants and townspeople strife, juridical confines of economic activity, and itemsmans and shoppers well-organized trade system at the villages formed peasants uninterested in enterprise. During the reforms season, in the villages, spread mobility trade forms. It was also influenced by the sparse web of townships, in possession of the right to organize markets and marts. But the liquidation of serfdom gave the way to enter the trade. Increasingly, peasants and townspeople were involved in the trade business. Simultaneously, the web of domestic trade increased—the number of markets, marts, and dolly-shops. While the web of domestic trade was spreading, the emporium became more available. Therefore, after the 1861 reforms, the demand for mobility trade forms at the markets declined. The consumers wanted to purchase necessaries of life every day and at a convenient time. This inside trade form, due to its impermanent timetable of work, could not satisfy. The increasing demands of the dwellers, the requirements of permanent realization of goods, roused by industrial production. Furthermore, the specialization of trade enterprises showed up. The products of agriculture and the goods of amateurs prevailed in the markets. The industrial production had to make its way to the market. To meet the needs, there were found more static trade companies. These companies, in the second part of the XIX century, took over some markets’ functions, especially like trade of industrial production and important goods.